1999
DOI: 10.1021/ie980732o
|View full text |Cite
|
Sign up to set email alerts
|

Computing Adsorption Isotherms for Benzene, Toluene, and p-Xylene in Heulandite Zeolite

Abstract: When computer simulations were performed in the grand canonical ensemble, adsorption isotherms for benzene, toluene, and p-xylene in Heulandite zeolite were constructed. Nitrogen adsorption was simulated to test a feasible computational strategy. Simulations were performed at three temperatures (200, 298, and 473 K), at pressures ranging from 0 to 200 kPa, and at water contents ranging from 0% to 4%. It was found that the adsorption of the organic species was not significantly affected by increasing the pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…cage‐like or channel‐like) and pore size (see for instance Refs. 74–82). At lower temperatures, however, the isotherms of benzene, toluene and p ‐xylene on MFI display increased capacities with a step or inflection point at about four molecules/unit cell83–85 (Fig.…”
Section: Mfi‐type Zeolite Membranes For Xylene Isomer Separationmentioning
confidence: 99%
“…cage‐like or channel‐like) and pore size (see for instance Refs. 74–82). At lower temperatures, however, the isotherms of benzene, toluene and p ‐xylene on MFI display increased capacities with a step or inflection point at about four molecules/unit cell83–85 (Fig.…”
Section: Mfi‐type Zeolite Membranes For Xylene Isomer Separationmentioning
confidence: 99%
“…Watanabe et al, 1995 . Adsorption of benzene on NaY, Heulandite, and MFI-type zeolites has also been studied ŽSnurr et al, 1994;Kitagawa et al, 1996;Klemm et al, 1998; . Laboy et al, 1999 . However, these studies did not involve the effects of -complexation on adsorption.…”
mentioning
confidence: 99%
“…Song et al [30] reported that the presence of mesopores in zeolite beta provides more space for adsorption and increases the adsorption capacity. Laboy et al [29] studied the adsorption of Bz, TOL, and PX in heulandite, with the increase of the water content from 0 to 4 %; the adsorption decreased significantly. Since a dry zeolite was used in this study, a larger space inside the adsorbent may be available for adsorption, which can lead to higher adsorption quantity.…”
Section: Adsorption Isothermsmentioning
confidence: 99%